Performance of calves born to beef cows seropositive but subclinical for bovine leukosis virus - Llewellyn, Donald A.; Teutemacher, K.L.; Marston, T.T.; Sanderson, M.W.; Hollis, Larry C. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Calves from a commercial beef herd were evaluated for weight gain differences based upon the bovine leukosis virus (BLV) serological status of their dams. One hundred forty-two multiparous cows from a commercial beef herd were tested for BLV by agar gel immunodiffusion. Eighty-nine cows (62.6%) were found to be seropositive for BLV. Weights were collected from all calves at weaning, from heifers on the date when selection of replacement heifers was made, and from steers on the day of harvest after being fed to finish weight in a feedlot. Offspring from seronegative cows tended to have heavier weaning weights (+17 lb) and heifer selection weights (+31 lb) than those from seropositive cows.
Keywords: Beef; Seropositive; Bovine leukosis virus